The Effect of Fineness of Segabai Rice Husk Ash PCC Cement Substitution in Concecrete Making - Fransisco, Vicky; Firdaus, Firdaus (PT ARRUS Intelektual Indonesia, 2025)
High quality concrete can be produced by increasing the porosity of the concrete . The porosity of concrete is influenced by the aggregate gradation and grain fineness . The limitations of the level of fineness of cement Grains are the main problem in producing high quality concrete , when viewed in terms of porosity for the addition of additional materials to the concrete mixture are used to change , improve the properties of concrete , increase the compressive strength of concrete . The additional materials used can be chemical ( chemical admixture ) and mineral ( admixture additives ). South Sumatra Province is an area that is one of the largest rice producers , this can be seen from the results of the Central Statistics Agency of South Sumatra Province in 2021 which showed that rice production in South Sumatra Province reached 2,552.44 thousand tons (BPS South Sumatra Province ). The method used is the experimental method by making samples and testing in the laboratory with targets of 0%, 5%, 10%, and 15% of the weight of cement and rice husk ash used . Each variation is made of 3 tests objects each with a size of 10 x 10 x 20 cm, for compressive strength testing at the ages of 7, 14, 28, 56 days . The results of the study on the use of rice husk ash show that the finer the rice husk ash , the compressive strength increases , but more rice​ husk ash is mixed , the compressive strength also decreases.